PENERAPAN MULTIPLE INTELLIGENCES PADA PELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI DALAM PENGUATAN SIKAP TOLERANSI PADA SISWA DI SD NEGERI 3 GADUNGAN TAHUN AJARAN 2024/2025 (Genta Hredaya: Media Informasi Ilmiah Filsafat Hindu, 2025)
Hindu Religious Education plays a vital role in shaping students’ character and tolerance. However, conventional teacher-centered methods often hinder this development. This study examines the implementation of the Multiple Intelligences strategy in Hindu Religious and Character Education at SD Negeri 3 Gadungan to strengthen students’ tolerance. A descriptive qualitative method with a phenomenological approach was used. The findings show that the strategy was applied through teaching modules based on students’ intelligence mapping. Supporting and inhibiting factors come from both internal and external aspects of the learning process. This strategy positively impacts the development of students’ tolerance in religious, social, and cultural contexts. It proves effective in promoting active participation and reinforcing character values in the learning process.
Keywords: Hindu religious education, Multiple intelligences, Attitude of tolerance